PERUMUSAN KONSEP IDENTITAS KABUPATEN SIDOARJO UNTUK CITY BRANDING MELALUI PENDEKATAN COMPETITIVE IDENTITY - R. Bhima Danniswara; Agung Eko Budiwaspada; Naomi Haswanto (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2020)
Identity is an important aspect in the formation of a city branding. The identity that is used as a basis in the formation of city branding must be unique compared to other cities. A positive city identity will reflect a positive city image in the minds of the audience. Formulation of city identity can be done by applying competitive identity theory to communicate positive messages to be conveyed to the audience, through the six channels of city identity. The ideal city identity must be formulated based on the facts that occur in the city itself. Result of this research is “connectedness” as representative identity for Sidoarjo. “Connectedness” can be used as a basis for Sidoarjo city branding design.